BOOK REVIEW: Călin Ioan Duşe, ‟A Healthy mind in a healthy body - Mens sana un corpore sano”, the second edition, revised and extended, Cluj-Napoca, Presa Universitară Clujeană, 2022, 536 p. - CRICOVEAN, Mircea (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2022)
The work A healthy mind in a healthy body – Mens sana in corpore sano, is the second revised and added edition of the homonymous book written by Călin Ioan Dușe. As the author confesses, this synthesis brings together some studies, which he has published over time, but also some chapters from published books, in such a way that they feed both the mind, but especially the soul. Also, in the introductory word, the author reasons that the genesis of the volume, which he offers to the public, can be found in the courses taught online to master’s students, in the academic year 2020-2021. After the introduction and the necessary critical notes, the author presents Education and education to the Romans, by which he concludes by saying that “the importance of Roman education was not limited to the small additions that it managed to bring to the classical education of the Hellenistic model, but especially by the fact that it managed to spread this model of education throughout the Empire over the centuries.”